2003
DOI: 10.1016/s0885-3924(03)00203-3
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic agents for the treatment of “death rattle” in patients with myasthenia gravis

Abstract: Difficulty clearing upper airway secretions (death rattle) is a frequent problem at the end of life. Treatment often includes the use of anticholinergic drugs. Myasthenia gravis is a disease characterized by muscle weakness and fatigue caused by an immune-mediated deficiency of acetylcholine receptors at the neuromuscular junction, and it is treated with anticholinesterase agents. We report the case of a patient dying of myasthenia gravis who had problems with the "death rattle" and who presented a dilemma as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
(7 reference statements)
0
4
0
Order By: Relevance
“…A case report by Kamel et al 8 described the successful management of nausea with oral cyclizine (12.5 mg twice a day) in a patient with myasthenia gravis. Anticholinergic agents 2,7 The use of anticholinergic medications, such as glycopyrronium and propantheline, is well defined in myasthenia gravis for the treatment of ''cholinergic'' side effects induced by acetylcholinesterase inhibitors. The use of anticholinergic agents for the palliative symptom management of patients with myasthenia gravis is, however, poorly defined.…”
Section: Case Summarymentioning
confidence: 99%
See 2 more Smart Citations
“…A case report by Kamel et al 8 described the successful management of nausea with oral cyclizine (12.5 mg twice a day) in a patient with myasthenia gravis. Anticholinergic agents 2,7 The use of anticholinergic medications, such as glycopyrronium and propantheline, is well defined in myasthenia gravis for the treatment of ''cholinergic'' side effects induced by acetylcholinesterase inhibitors. The use of anticholinergic agents for the palliative symptom management of patients with myasthenia gravis is, however, poorly defined.…”
Section: Case Summarymentioning
confidence: 99%
“…The use of anticholinergic agents for the palliative symptom management of patients with myasthenia gravis is, however, poorly defined. A case report by Spiess et al 7 reported the safe and successful use of topical scopolamine for excessive oropharyngeal secretions in a patient with myasthenia gravis.…”
Section: Case Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Other drugs that can assist with reducing secretions are atropine, glycopyrrolate, and hyoscyamine (Bennett et al, 2002;Spiess & Scott, 2003). In addition to those agents, diuretics such as furosemide can eliminate excess fl uids that build up in the upper airways.…”
Section: Rattlementioning
confidence: 99%